2011
DOI: 10.1038/ncomms1254
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-dependent gating of a voltage-gated potassium channel

Abstract: Recent studies hypothesized that phospholipids stabilize two voltage-sensing arginine residues of certain voltage-gated potassium channels in activated conformations. It remains unclear how lipids directly affect these channels. Here, by examining the conformations of the KvAP in different lipids, we showed that without voltage change, the voltage-sensor domains switched from the activated to the resting state when their surrounding lipids were changed from phospholipids to nonphospholipids. Such lipid-determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
95
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 58 publications
9
95
0
Order By: Relevance
“…Under such conditions, the channels with their intracellular side facing outside (the opposite of what we (Fig. 5 C, black arrow; Zheng et al, 2011). As a positive control, we showed that the L125C KvAP in bSUMs treated with detergents was reactive, probably because of the mobility of the voltage-sensor domains in the detergents (Fig.…”
Section: Favored Directional Insertion Of Tetrameric Channel Proteinssupporting
confidence: 47%
See 2 more Smart Citations
“…Under such conditions, the channels with their intracellular side facing outside (the opposite of what we (Fig. 5 C, black arrow; Zheng et al, 2011). As a positive control, we showed that the L125C KvAP in bSUMs treated with detergents was reactive, probably because of the mobility of the voltage-sensor domains in the detergents (Fig.…”
Section: Favored Directional Insertion Of Tetrameric Channel Proteinssupporting
confidence: 47%
“…the proteinaceous parts are solely responsible for voltagedependent function. Recent studies, however, recognize that lipids play critically important roles in the controlled opening or closing (gating) of these ion channels (Ramu et al, 2006;Schmidt et al, 2006;Schmidt and MacKinnon, 2008;Xu et al, 2008;Zheng et al, 2011;Jiang and Gonen, 2012;Brohawn et al, 2014;Hite et al, 2014). Compelling evidence from these studies suggests that lipids surrounding a voltage-gated potassium (Kv) channel exert strong gating effects on the channels by directly affecting the energetics behind the conformational changes of the voltage-sensor domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data have been reported on the functionally modifying effects of membrane lipids on channel proteins that result in the gating equilibrium being altered (6,(9)(10)(11)(12)(13). In voltage-gated channels, the voltage-sensor domain (VSD) primarily senses changes in the membrane electric field, but this sensing is modulated by the lipid composition (9,11,13).…”
mentioning
confidence: 99%
“…In voltage-gated channels, the voltage-sensor domain (VSD) primarily senses changes in the membrane electric field, but this sensing is modulated by the lipid composition (9,11,13). For the non-voltage-gated (the twotransmembrane-helix inward-rectifier type) channels, such as the KcsA potassium channel from Streptomyces lividans, the underlying mechanism of the effect exerted by lipids is still undergoing extensive investigation, even though the structural information on the channel proteins cocrystallized with lipid molecules has already been reported (14)(15)(16)).…”
mentioning
confidence: 99%